Camel Ratio On Profitability Banking Performance (Malaysia Versus Indonesia) - Maryam binti Badrul Munir; Ummi Salwa Ahmad Bustamam (GIAP Journals, 2024)
Purpose: This research analyzed about profitability banks performance based on the CAMEL (Capital Adequacy, Asset Quality, Management, Earnings and Liquidity) on the Bank's profitability. Capital adequacy measured by debt equity ratio (DER) and non-performing loans (NPL), asset quality measured by return on assets (ROA), management will be measured by cost per income, earnings measured by return on equity (ROE) and liquidity measured by interest expense and deposit. Methodology: The samples were 114 samples (from 10 bank in Malaysia and 9 bank in Indonesia) since 2010-2015. This analysis used descriptive method and multiple regression analysis, the result of this research indicated that banking profitability have a good performance based on CAMEL analysis. Findings: From the results of regression, the CAMEL analysis has a significant relationship to the bank profitability Practical Implications: The study demonstrated the use of CAMEL analysis to measure bank profitability. If bank performance declining through the CAMEL analysis so the Bank should make a decision to make a better performance changes of banking. Social Implications: This study was about the importance of camel analysis measuring the performance banking. CAMEL analysis detected the decrease in performance in any business sector.